Examining the implementation of total quality management principles in selected Algerian higher education education institutions - Kamel, Haddou (Kulliyyah of Education, International Islamic University Malaysia, 2019)
This study aims to examine the levels and effectives implementation of Total Quality Management principles in the Algerian Higher Education Institutions based on the perspective of some academic lecturers. The survey design research method used in this study was based on Likert scale survey questionnaires to collect the data. The questionnaires were quoted from a previous study and were modified according to the study requirements, and were distributed to 220 academic lecturers .The results revealed that (1) the majority of respondents from the research see that the synergistic relationship of Total Quality Management principles was high (2) there was no Significant difference between genders and academic qualifications, but there was a significant difference in terms of age and years of experience (3) there were no statistically significant differences in the application of the principles of Total Quality Management in the mentioned universities in this study (4) the majority of the academic universities lecturers realized that the implementation of the principles of Total Quality Management in Algeria has not been effective to improve the quality of higher education institutions. The findings of this study are important to the exerted efforts by the Algerian government in the future of Higher Education.